(untitled) (Transport systems and technologies, 2019)
The implementation of the sale and purchase contract means the obligation of one of the parties of the said contract to organize the transportation of the cargo by sea. It actually means the necessity to charter the vessel. The engagement of the vessel to carry the cargo is searched as a three-stage process among which the negotiations are consider to be the main one. At the same time the first one – forming the requirements for the vessel, and the last one – preparation the final version of the charter-party – are rather quick in execution and last not for a long time The chartering process is formalized with the modalities of temporal logic which helped to identify the beginning and final moments of each stage of the vessels engagement process and to formalized their causal relations. Such structure definition of the searched process can be used as a base for charterer’s time management as far as hi has some obligations and/or interests regarding the terms of the cargo delivery.